Active Learning in the Heureka Project — Teachers in the Role of Students - Dvořáková, Irena (Scientia in educatione, 2017)
Our long-term Heureka project is based on the principle of active work in learning and teaching — both at school with students and in teacher training. Teachers in our seminars work the same way as students at schools — solving the same problems, doing the same experiments and sometimes even making the same mistakes. Our seminars provide longterm systematic training — the cycle of seminars for new participants takes ten weekends during the course of two years. That gives all participants the possibility and especially the time to change their approach to teaching physics. The character of our seminars is rather informal: the seminars are free of charge and teachers join Heureka on a voluntary basis, gaining no formal advantages or beneﬁts at their schools. The seminars take place during weekends, with teachers staying (and sleeping) in classrooms. In the autumn of 2012, we started already the 6th seminar cycle. Over the years, we have built a network of about 150 active teachers who have the possibility to meet at various advanced seminars and at “The Heureka Workshops” annual conference. The conference regularly attracts more than 100 participants and includes international guests. We are convinced that our experience could be interesting and inspiring for other people working in physics education in diﬀerent countries.